A new species of Dryocalamus (Serpentes: Colubridae) endemic to the rainforests of southwestern Sri Lanka - Wickramasinghe, L.j. Mendis; Vidanapathirana, Dulan Ranga; Pushpamal, Vishan; Wickramasinghe, Nethu (Zootaxa, 2020)
We describe a new species of Dryocalamus based on two specimens collected from the wet zone rainforests of southwestern Sri Lanka. Dryocalamus chithrasekarai sp. nov., is distinguished from congeners by its colour pattern (anterior body with solid white bands and a checkered appearance on the posterior lateral body, with consecutive bands coalescing along the ventrolateral margin; posterior margin of the nuchal band flat); the absence of a preocular scale; loreal in contact with supraocular; dorsal scales smooth and in 15 straight rows; cloacal shield divided. In addition, we find that previous records of Dryocalamus gracilis are probably spurious.